2001
DOI: 10.1088/0953-2048/15/1/317
|View full text |Cite
|
Sign up to set email alerts
|

Spray pyrolysis of epitaxial YBCO films on (100) single crystal SrTiO3substrates

Abstract: Biaxially textured films of YBa 2 Cu 3 O 7−∂ have been deposited in situ on (100) single crystal SrTiO 3 substrates by a one step spray pyrolysis process. Good out-of-plane (FWHM = 0.4 • ) and in-plane (FWHM = 8 • ) textures have been achieved for films grown at temperatures between 800 • C and 900 • C, at atmospheric pressure. The ac susceptibility measurements have shown that the films have T c onsets of 90 K without the need of a subsequent oxygenation procedure. Magneto-optic imaging studies have indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 16 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…They showed that strong texturation was possible on textured silver; this was further confirmed by Schindl et al [22]. At the same time, Shields et al [23] showed similar results on STO. The best results obtained to date was by Ferreri et al [24] who reached J c = 5 × 10 5 A cm −2 (at 77 K measured by screening current probed by Hall imaging) after using a slightly more concentrated solution than reported in their previous paper [20].…”
Section: Spray Pyrolysis For Ybco Hts Filmsmentioning
confidence: 67%
“…They showed that strong texturation was possible on textured silver; this was further confirmed by Schindl et al [22]. At the same time, Shields et al [23] showed similar results on STO. The best results obtained to date was by Ferreri et al [24] who reached J c = 5 × 10 5 A cm −2 (at 77 K measured by screening current probed by Hall imaging) after using a slightly more concentrated solution than reported in their previous paper [20].…”
Section: Spray Pyrolysis For Ybco Hts Filmsmentioning
confidence: 67%
“…This frequency produces droplet sizes of 2-3 μm. 22 The aerosol was sprayed with an argon transport flow (70-250 l h −1 ) onto the substrate heated at 850-915 °C. The deposition time varied from 1 min to 1 h. After deposition, an in situ annealing was made at the same temperature for various times (0, 15, 30, 60, 120, 240, 480 minutes).…”
Section: Processing For the Preparation Of The Filmmentioning
confidence: 99%
“…This result was confirmed by our measurements and by other research groups. 22 Several works [22][23][24][25][26] on various types of substrates have shown that biaxially textured YBCO thick films can be spray deposited in situ at high temperature (850-920 °C) without requiring an ex situ post-annealing step. The critical current densities in the films deposited in this method mostly exceed 10 5 A cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…Several physical and chemical processes have been used to prepare the thin films, including pulsed laser ablation [10], molecular beam epitaxy [11,12], sol-gel [13,14], spin coating [15,16] and spray pyrolysis [17][18][19][20][21][22]. Among them, the spray pyrolysis technique was chosen because it has a number of advantages.…”
Section: Introductionmentioning
confidence: 99%